Manajemen Interferensi Femtocell Menggunakan Metode Fractional Frequency Reuse (FFR) pada Jaringan Ultra-Dense Network (UDN) dengan Sektorisasi Macrocell - Sitronella Nurfitriani Hasim; Novalia Pertiwi; Adinda Azzahra; Anggrit Dewangkara Yudha Pinangkis; Soraida Sabella; Muhammad Rizky Hikmatullah; Aji Pamungkas Tri Nurcahyo (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2026)
The development of 5G technology with the implementation of Ultra Dense Network (UDN) has brought new demands in interference management and frequency spectrum allocation. The main challenge faced is the high level of inter-cell interference, especially between macrocells and femtocells in highly dense network environments. This study applies the Fractional Frequency Reuse (FFR) method for interference management in downlink femtocell networks, allocating 4 sub-frequencies to 3 sectors in the cell edge area and 1 sector in the cell center. The probability of SINR below 15 dB successfully decreased from 100% to 0%, throughput below 100 Mbps dropped from 100% to 0%, while BER above 0.01 decreased from 100% to 0%, with a minimum value reaching 10⁻¹³. The optimal performance of this sector is supported by the implementation of a method that eliminates cross-tier interference. SINR values are directly proportional to throughput and inversely proportional to BER.